Synthesis of U-theraphotoxin-Pv1a_1, an Aedes aegypti larvicidal disulfide bridged peptide from the Colombian tarantula Pamphobeteus verdolaga (Araneae: Theraphosidae) - Sebastián Estrada-Gómez; Cristian Salinas-Restrepo; Leidy Johana Vargas-Muñoz; Fanny Guzmán; Cesar Segura; Davinia Pla; Libia Sanz; Juan J Calvete (Toxicon: X)
The attention to the increased resistance of Aedes aegipty to traditional insecticides has been directed to the development of bioinsecticides, such as those produced by insect predators, e.g. spiders. Here we present the solid-phase synthesis of native U-theraphotoxin-Pv1a_1 (n-Pv1a_1) from Pamphobeteus verdolaga, an active (by contact) insecticidal peptide against A. aegipty. U-theraphotoxin-Pv1a_1 sequence was gathered from venom proteomics and venom gland transcriptomics of Pamphobeteus verdolaga, and synthesized by solid phase using the Fmoc strategy followed by dimethyl sulfoxide promoted native disulfide bond formation. The synthetic peptide (s-Pv1a_1) was assayed for larvicidal activity in II and III instar A. aegypti larvae, as well as for cytotoxicity in human red blood and HaCat cells. s-Pv1a_1 showed potent activity towards A. aegypti larvae in the micro molar range, while showing no hemolytic activity and mild cytotoxicity to HaCat cells. Its potent contact activity makes n-Pv1a_1 and its synthetic version, s-Pv1a, promising biopesticides for the control of mosquito populations.